2007
DOI: 10.1080/08860220701260636
|View full text |Cite
|
Sign up to set email alerts
|

Higher Incidence of Cholelithiasis in Chronic Renal Failure Patients with Secondary Hyperparathyroidism Undergoing Peritoneal Dialysis

Abstract: We found that the incidence of CL in CRF-PD patients with secondary hyperparathyroidism was higher than CRF-PD patients with normal PTH levels. It was also detected that female gender, high creatinine levels, and elevated PTH levels might influence the development of CL in CRF-PD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Chronic liver disease is a well-recognized risk factor for cholelithiasis [4,23]. Fatty liver [12], hepatitis B [16,22], hepatitis C [6,29], elevated ALT levels [15], and cirrhosis [22,30,31] have all been found to be related to cholelithiasis in different small studies. In Taiwan there is known to be a higher prevalence of viral hepatitis than in other regions [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic liver disease is a well-recognized risk factor for cholelithiasis [4,23]. Fatty liver [12], hepatitis B [16,22], hepatitis C [6,29], elevated ALT levels [15], and cirrhosis [22,30,31] have all been found to be related to cholelithiasis in different small studies. In Taiwan there is known to be a higher prevalence of viral hepatitis than in other regions [32].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between chronic kidney disease and cholelithiasis continues to be investigated [30,45]. Chronic kidney disease may alter plasma concentrations of electrolytes, including calcium.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, abnormal bile metabolism along with a low-protein diet has been suspected to cause the high prevalence of GBS among CKD5 patients. Secondary hyperparathyroidism was reported to be another potential candidate for the promotion of GBS formation in end-stage CKD patients [18]. Inflammation is also a possible risk factor for GBS formation.…”
Section: Discussionmentioning
confidence: 99%
“…Barut et al reported that secondary hyperparathyroidism might influence the development of cholelithiasis in chronic renal failure-peritoneal dialysis patients [1]. These results suggest that secondary hyperparathyroidism caused by hypercalciuria in furosemide use or Bartter syndrome could be one of the important factors in the development of cholelithiasis.…”
mentioning
confidence: 92%